Advanced Strategies for Container Orchestration in Multi - Cloud Environments: Towards Enhanced Performance, Scalability, and Resilience - Jose, Sebastian (Journal of Research in Science and Engineering, 2025)
In the era of distributed cloud computing, effective container orchestration is crucial for managing workloads across multiple cloud platforms, ensuring optimal performance, scalability, and resilience. This paper explores advanced strategies for container orchestration in multi - cloud environments, focusing on techniques such as dynamic resource allocation, automated workload distribution, and fault tolerance mechanisms. By examining and extending orchestration platforms like Kubernetes and OpenShift to operate seamlessly across diverse cloud providers, the study aims to minimize vendor lock - in while maximizing resource efficiency. [1] Additionally, it addresses key challenges including network latency, data synchronization, and security, and presents best practices for maintaining high availability and robust disaster recovery. Through a comprehensive analysis and empirical evaluations, the research demonstrates how leveraging multi - cloud container orchestration can enhance operational agility, improve application reliability, and achieve a more balanced and efficient cloud architecture.